Computational Efficacy of Artificial Intelligence Model for in Silico Vaccine Development - Jojare, Renuka Anil; Jadhav, Mahadev Asaram; Chavan, Dipak Pandit (Journal for Research in Applied Sciences and Biotechnology, 2024)
Bioinformatics is an interdisciplinary branch of science that develops methods and software tools for understanding biological data. Bioinformatics include both the power of biological concept and computational method to solve biological problem. It also bridged biological field with speed and accuracy of computer. Pre-design of vaccines by using artificial intelligence model for future upcoming viruses. Using AI throughout the vaccine development process to ensure that virus/pathogen vaccine met the needs of individuals without spending much time. A piece of genetic code that is capable of copying itself and typically has a detrimental effect on body, the pre-design vaccines will be available on one click no need for direct trials on humans. The model gives the predicted information about the upcoming risks for transmitting the disease in future generations by using artificial intelligence. The model is based on artificial intelligences and bioinformatics filed, all data will be presented and analyze simultaneously by the model and will efficiently build the vaccine molecule against the virus. The model provides highest accuracy and speed to sort out the vaccine.